A quality-of-service evaluation method based on the cloud model for routing protocols in wireless sensor network - Wenxian Jiang; Chenzhe Gu; Jingjing Wu (International Journal of Distributed Sensor Networks)
The routing layer quality of service in wireless sensor network depends on different indices such as throughput, delay, packet loss rate, energy consumption, and degree of congestion. A single index does not adequately reflect the real quality of service while an excessive number of indices increase the complexity of the evaluation model. In addition, existing quantitative evaluation methods can lead to under-fitting or over-fitting. In this article, we present a comprehensive qualitative quality-of-service evaluation method based on the cloud model. Using Gaussian cloud transformation, each quality-of-service index can be divided into several qualitative concepts (cloud models). Concepts belonging to different indices can be combined together to evaluate the quality of service. We use a frequent-pattern tree approach to mine association rules of quality-of-service concepts and arrive at a suitable decision. This method simplifies the evaluation model by transforming a numeric value to its equivalent qualitative concept and brings out the internal relationships among different quality-of-service indices according to the association rules. Besides, it automatically finds a common standard to evaluate and compare different routing protocols simultaneously. The evaluation results show that the proposed method provides a good quality-of-service assessment when applied to different routing protocols.